A study on multi frequency operation of RF transmission system for EC H&CD system. (7th September 2018) - Oda, Yasuhisa; Anderson, James; Doane, John; Kajiwara, Ken; Ikeda, Ryosuke; Takahashi, Koji; Sakamoto, Keishi
Abstract: To study the performance of multi frequency operation of transmission lines for electron cyclotron heating and current drive (EC H&CD) systems, the performance of a transmission line (TL) with 104 GHz/137 GHz/170 GHz operation was evaluated using a multi frequency gyrotron. The TL test stand for multi frequency high-power operation was composed from corrugated waveguides with 63.5 mm inner diameter and TL components, such as miter bends. The coupling efficiency of gyrotron power into the TL inlet, mode purity at the TL end, and power transmission efficiency were measured for three frequency operations. The transmission efficiency of the 40 m length TL remained at 94%–95% for three frequencies and that of the MOU varied because of the quasi-optical design in the MOU. The mode conversion in TL was found to be less than 2% for three frequencies. These results indicate that the TL using corrugated waveguide can deliver radio frequency power from the gyrotron to the launcher with similar performance expected in single frequency operation in ITER.